Respostas
respondido por:
1
x²-3x+1
-4 - 3(4)+1
-4-12+1
-16+1
-15
b. a²+ b²/a-b
(-3)²+(3)²=-3-3
9+9=9
18=9
9/18
1/2
-4 - 3(4)+1
-4-12+1
-16+1
-15
b. a²+ b²/a-b
(-3)²+(3)²=-3-3
9+9=9
18=9
9/18
1/2
BielStuart:
ele está elevado a um expoente par então ele não e negativo
respondido por:
1
A) x²-3 x +1
-4² - 3 (-4) + 1
16+12+1
=29
b)-3²+ 3²/-3-3
=9=9/-6
=18/-6
= -3
-4² - 3 (-4) + 1
16+12+1
=29
b)-3²+ 3²/-3-3
=9=9/-6
=18/-6
= -3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás